Base editing rescues acid α-glucosidase function in infantile-onset Pompe disease patient-derived cells - Chloe L. Christensen; Shih-Hsin Kan; Perla Andrade-Heckman; Allisandra K. Rha; Jerry F. Harb; Raymond Y. Wang (Elsevier, 2024)
Infantile-onset Pompe disease (IOPD) results from pathogenic variants in the GAA gene, which encodes acid α-glucosidase. The correction of pathogenic variants through genome editing may be a valuable one-time therapy for PD and improve upon the current standard of care. We performed adenine base editing in human dermal fibroblasts harboring three transition nonsense variants, c.2227C>T (p.Q743∗; IOPD-1), c.2560C>T (p.R854∗; IOPD-2), and c.2608C>T (p.R870∗; IOPD-3). Up to 96% adenine deamination of target variants was observed, with minimal editing across >50 off-target sites. Post-base editing, expressed GAA protein was up to 0.66-fold normal (unaffected fibroblasts), an improvement over affected fibroblasts wherein GAA was undetectable. GAA enzyme activity was between 81.91 ± 13.51 and 129.98 ± 9.33 units/mg protein at 28 days post-transfection, which falls within the normal range (50-200 units/mg protein). LAMP2 protein was significantly decreased in the most robustly edited cell line, IOPD-3, indicating reduced lysosomal burden. Taken together, the findings reported herein demonstrate that base editing results in efficacious adenine deamination, restoration of GAA expression and activity, and reduction in lysosomal burden in the most robustly edited cells. Future work will assess base editing outcomes and the impact on Pompe pathology in two mouse models, Gaac.2227C>T and Gaac.2560C>T.